Decision Making of Spare Parts Inventory Based on Risk Quantification - Kamal Imran Sharif; Jafni Azhan Ibrahim; Zulkifli Mohamed Udin; Abdul Aziz Othman (International Journal of Supply Chain Management, 2016)
Financial losses due to spare part breakdown in plant operation have created an upsetting situation among stakeholders. The failure increase the cost of repair and production downtime. . Obviously, maintenance planner tends to increase the spare part inventory level in order to meet the operational requirement and this in return has increased the inventory cost. The maintenance and inventory function is important in order to ensure the plant operate accordingly. Moreover, it is necessary for the plant maintenance to balance the issue of shortage and excess of inventory in plant maintenance. In view of this situation, the spare parts become a critical matters and it is good starting point to tackle the issues from looking at the perspective of spare parts inventory risk. This paper explain about the development of risk based technique using the shortage and excess situation of spare parts inventory by using the Breakdown Probability Table to quantify the risk for decision making purpose.